2021
DOI: 10.23876/j.krcp.21.012
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in highly sensitized recipients

Abstract: In kidney transplantation (KT), overcoming donor shortage is particularly challenging in patients with preexisting donor-specific antibodies (DSAs) against human leukocyte antigen (HLA), called HLA-incompatible KT (HLAi KT), carrying the risk of rejection and allograft loss. Thus, it is necessary to accurately evaluate the degree of sensitization before HLAi KT, and undertake appropriate pretreatment strategies. To determine the degree of sensitization, complement-dependent cytotoxicity has been the only metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Out of these, patients who experienced allograft loss within 90 days (n = 7), who were sensitized to donor human leukocyte antigen (HLA) before KT (n = 126), and whose CDR calculation was not possible due to missing TAC-C0 results (n = 14) were excluded from the present study. Sensitization to donor HLA was defined as positivity to the complement-dependent cytotoxicity cross-match test, flow cytometry cross-match test, or the presence of DSA with a median fluorescence intensity (MFI) of ≥ 1,000 before KT ( 18 ). Ultimately, 1,080 patients were included in the study, the last follow-up date was December 31, 2020, and the mean follow-up duration of these patients was 5.7 years.…”
Section: Methodsmentioning
confidence: 99%
“…Out of these, patients who experienced allograft loss within 90 days (n = 7), who were sensitized to donor human leukocyte antigen (HLA) before KT (n = 126), and whose CDR calculation was not possible due to missing TAC-C0 results (n = 14) were excluded from the present study. Sensitization to donor HLA was defined as positivity to the complement-dependent cytotoxicity cross-match test, flow cytometry cross-match test, or the presence of DSA with a median fluorescence intensity (MFI) of ≥ 1,000 before KT ( 18 ). Ultimately, 1,080 patients were included in the study, the last follow-up date was December 31, 2020, and the mean follow-up duration of these patients was 5.7 years.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-transplant DSZ protocol. Our center's DSZ protocol has been presented previously 12,32,35 . Brie y, we used strati ed protocol according to the baseline MFI value.…”
Section: Study Populationmentioning
confidence: 99%
“…Therefore, currently used desensitization (DSZ) techniques are based on the MFI value of HLA-DSA in addition to XM test result [10][11][12] . However, when LSA assay is positive and XM test is negative, the clinical relevance of HLA-DSA on post-transplant clinical outcomes remains controversial [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…This improvement allows for more detailed risk stratification for the prediction of ABMR or allograft failure than a traditional XM test [ 8 10 ]. Therefore, current desensitization strategies are based on the MFI values of HLA-DSA and XM test results [ 11 13 ]. However, previous studies on the clinical impact of HLA-DSA on posttransplant clinical outcomes have shown contradictory results in case the LSA assay is positive and the XM test negative [ 14 17 ]; therefore, its clinical impact remains unclear.…”
Section: Introductionmentioning
confidence: 99%